Unintended Consequences of Productivity Improvement Strategies on Safety Behaviour of Construction Labourers; A Step toward the Integration of Safety and Productivity - Ghodrati N; Yiu TW; Wilkinson S; Poshdar M; Talebi S; Elghaish F; Sepasgozar SME (MDPI (Basel, Switzerland), 2022)
Abstract The construction industry is facing constant pressure to improve its poor safety record and low productivity rate. A significant amount of research has been undertaken to identify the best practices to enhance productivity and safety. Nevertheless, the mainstream research in the field of construction focuses on one of these issues rather than implementing a holistic approach to resolve them. Consequently, the interactions between productivity and safety cannot be fully understood. Recent studies have demonstrated that management strategies and practices for improving labour productivity can trigger a series of unintended consequences that affect safety performance in construction projects. However, the behavioural aspects of these unintended consequences have yet to be investigated. This research addresses the gap by measuring the impacts of seven management strategies for improving labour productivity on the safety behaviour of construction labourers. A total of 191 construction labourers participated in a survey designed based on the Management Strategy Assessment Index (MSAI). The results show that the implemented management strategies for improving labour productivity have a greater impact on shaping safety compliance (SC) behaviours than safety participation (SP) behaviours of labourers. This study took a further step by breaking down the management strategies to their constitutive practices and measuring their impacts on SC and SP, and labour productivity. This paper provides further insight into the complex relationship between the productivity and safety behaviour of construction labourers. The findings can help project managers to improve labour productivity without harming their safety unintentionally.
Keywords: construction safety; safety behaviour; labour productivity; management strategies